Regulation of histone H4 acetylation in the CNS and defensive behavior command neurons of the mollusk Helix mediated by serotonin and neuropeptide FMRFamide - L. N. Grinkevich; T. G. Zachepilo (Вавиловский журнал генетики и селекции)
Epigenetic mechanisms are commonly known to underlie memory formation. Presently, scientists’ attention is focused on changes in the levels of histone modifications (mainly acetylation and methylation) in the chromatin of CNS cells tested in various experimental models. Owing to their relatively simple CNSs, mollusks are among the most popular models. Our experiments were con-ducted with the mollusk Helix lucorum because its CNS had been investigated in detail and most of its neurons had been proven to participate in the formation of different behavior patterns, including the prolonged response to various stimuli. This work concerns the influence of various effectors (serotonin and FMRFamide, associated with CNS activator and inhibitory pathways, respectively) on the acetylation of H4 histone in the subesophageal ganglion complex and in defensive behavior command neurons of the right and left parietal ganglia (RPa3/2 and LPa3/2) in the snail. Western blot analysis showed that FMRFamide inhibited histone H4 acetylation induced by serotonin in the subesophageal complex of CNS ganglia. However, serotonin and FMRFamide cooperatively enhanced the induction of histone H4 acetylation in RPa3/2 defensive behavior command neurons. No changes were found in the counterpart LPa3/2. It is a new piece of evidence for functional asymmetry in Helix. The inhibitory pathways mediated by FMRFamide not only inhibit the activatory intracellular processes in the entire CNS but can also enhance them, as in RPa3/2 defensive behavior command neurons.